PERANCANGAN METODE HUMAN CENTERED DESIGN USER INTERFACE DAN USER EXPERIENCE PADA SISTEM HARGA KEBUTUHAN POKOK KABUPATEN MALANG - Eka Wahyudi, Desantara; Budianto, Alexius Endy; Ahsan, Moh (Prodi Teknik Informatika, Fakultas Sains dan Teknologi, 2025)
The Ministry of Communication and Information with all its diverse society requires overlapping in terms of equalizing services, especially in terms of data information. The problem is caused by inaccurate data information so that the asset data used as the basis of the data affects the data information received which does not match the field conditions. The running of data processing so far is still based on technicalities that tend to be conventional so that a capable system is needed to accommodate the problem. By using a mixed method, this study uses Human Centered Design as the basis for designing an application design called SIHARKEPO (Basic Needs Price Information System). This study will later focus on two main problems, namely the SIHARKEPO user interface design process and the analysis of users of the Basic Needs Price Information System (SIHARKEPO) in providing data information to users. The results of this study are concrete applications that can be applied to the process of providing basic needs price information data services and make it easier for the public to obtain them.